PERFORMA KOROSI BAJA KARBON PADA UJI SIMULASI PIPA UNTUK SISTEM SALURAN AIR PENDINGIN [CORROSION PERFORMANCE OF CARBON STEEL IN PIPE SIMULATION TEST FOR COOLING WATER SYSTEMS] - Royani, Ahmad (Metalurgi, 2019)
The main problem in cooling water systems in geothermal power plant units is supported by corrosion, deposits, and slime. Corrosion can shorten the life of cooling water system equipment due to a decrease in operating efficiency, leakage, and pollution. These problems, occur very complex and many causes. On the other hand, most cooling water systems in the industry contain carbon steel components that are easily corroded. To determine the value of the corrosion rate of carbon steel in a geothermal power plant, a simulation test using an open recirculating system was carried out. The simulation process is done by an interval test method and based on NACE RP0775 standard. The corrosion rate of those steel was determined by weight loss method. The Morphology of surface and composition of corrosion products are characterized using scanning electron microscopy (SEM), X-ray diffractometer (XRD) and energy dispersive spectroscopy (EDS). The corrosion rate values of carbon steel from the simulation results for 1, 3 and 4 weeks were 2.29 mmpy; 1.23 mmpy; and 0.93 mmpy, respectively. There is a decrease in the corrosion rate of the simulation time is extended, because of passive film layers on the steel surface. Meanwhile, the most dominant water parameters in this simulation are dissolved oxygen (DO). The change of DO greatly affect the corrosion rate of carbon steel. Based on the product morphology of corrosion, corrosion attacks occur locally. Corrosion products form oxide compounds in the form of Fe3O4, FeOOH, and Fe2O3. AbstrakMasalah utama dalam sistem pendingin air dalam unit pembangkit listrik panas bumi meliputi korosi, deposit dan slime (lendir). Korosi dapat memperpendek umur pakai peralatan sistem pendingin air karena mengakibatkan penurunan efisiensi operasi, kebocoran dan polusi. Masalah-masalah tersebut sangat komplek dan banyak faktor penyebabnya. Di sisi lain, sebagian besar sistem air pendingin di industri mengandung komponen baja karbon yang mudah terkorosi. Untuk mengetahui nilai laju korosi baja karbon pada unit pembangkit listrik panas bumi, maka dilakukan uji simulasi menggunakan sistem resirkulasi air terbuka pada temperatur 37 °C. Proses simulasi dilakukan dengan metode interval test dan berdasarkan standar NACE RP0775. Laju korosi baja tersebut diukur dengan metode pengurangan berat. Morfologi permukaan dan komposisi produk korosi dikarakterisasi menggunakan SEM (scanning electron microscopy), XRD (x-ray diffraction) dan EDS (energy dispersive spectroscopy). Nilai laju korosi baja karbon hasil uji simulasi selama 1, 3 dan 4 minggu masing-masing sebesar 2,29 mmpy; 1,23 mmpy; dan 0,93 mmpy. Terjadi penurunan laju korosi jika waktu simulasi diperpanjang akibat terbentuknya lapisan produk korosi pada permukaan baja. Sementara itu, parameter air yang paling menentukan laju korosi adalah DO (dissolved oxygen). Perubahan DO sangat mempengaruhi kecepatan laju korosi. Berdasarkan morfologi produk korosi, serangan korosi terjadi secara lokal yang sebarannya merata. Produk korosi berupa senyawa oksida dalam bentuk Fe3O4, FeOOH dan Fe2O3.